Revisiting the Equity Promise of School Zoning Policies in Indonesia: Between Idealism and Implementation - Sisilia Putri Adinda (Jurnal Pendidikan Sosial Indonesia, 2025)
Purpose – This study critically examines the impact of Indonesia's school zoning policy on efforts to achieve social justice in education. Although the policy was designed to distribute educational access more equitably, its implementation has revealed unintended disparities and new forms of inequality. The research focuses on the gap between the normative goals of the policy and its practical outcomes, especially in terms of distributive justice. Design/methods/approach – A qualitative approach was employed using a systematic literature review design. Data were collected from peer-reviewed academic articles, policy reports, and relevant documents. Thematic analysis was used to identify recurring patterns related to the implementation of zoning policy in different Indonesian regions. Findings – The study identified four key findings: the zoning policy has expanded educational access for students from low-income families; however, quality disparities among schools within zones persist; the policy’s effectiveness is shaped by local capacity and spatial planning; and the policy has generated new social dynamics within school communities. These findings suggest that equitable education requires more than geographic distribution—it demands structural and systemic reform. Research implications/limitations – This study is limited to recent literature within the last five years and does not include primary field data. Nevertheless, it offers significant insights into the evaluation of zoning-based education policies and emphasizes the need for locally responsive implementation strategies and comprehensive institutional capacity development.